Formulación de cerveza artesanal tipo "ale" a partir de maíz (zea mays) como alternativa a la producción local de cerveza artesanal y a la importación de maltas - Arias Espinoza, Luis Alberto (Machala : Universidad Técnica de Machala, 2024)
In Ecuador, both industrial and craft breweries import malt for brewing their beers, resulting in a significant outflow of foreign currency due to the importation of this raw material. Therefore, the primary objective of this thesis was to formulate a craft corn Ale beer with a partial substitution of corn malt for barley malt. This substitution serves as an alternative to local beer production and malt importation while ensuring sensory acceptability by consumers. For the beer production process, a base formulation was utilized, drawing references from the ingredients typically found in American Brown Ale style beer. This beer style is renowned for its dark appearance derived from dark malts, distinctive hop aroma, and robust body. Mix designs were created using the Design Expert program for each corn variety. The factors considered for the “Chulpi” variety included the percentage of “Chulpi” corn malt (%CM) and Pale Ale barley malt (%BM), while for the “Blanco Blandito” variety, it involved the percentage of “Blanco Blandito” corn malt (%BBM) and Pale Ale barley malt (%BM). The response variable under scrutiny was the overall impression. Statistical tests were conducted at a 95% confidence level using the Minitab® statistical software version 19. Both corn varieties underwent malting using an adapted barley malting process, meticulously controlling parameters such as temperature, time, and humidity (ranging between 38°C-31°C, 3-5 days, and 53% HR). Following this process, germinated corn was obtained, accounting for 93% for the “Chulpi” variety and 85% for the “Blanco Blandito” variety, respectively. Subsequently, the germinated corn underwent a controlled drying process, ensuring optimal conditions of time and temperature (24 hours at 65°C). Proximal analysis of each malted corn variety, encompassing parameters such as moisture, carbohydrates, protein, lipids, fiber, ash, acidity, and pH, revealed a higher concentration of carbohydrates in the “Blanco Blandito” variety. The efficiency of the applied treatments was thoroughly compared, with the TC70 treatment emerging as the most efficient for the “Chulpi” variety (comprising 70% malted corn and 30% barley malt). Meanwhile, for the “Blanco Blandito” variety, the TB70 treatment yielded the best results, albeit with no significant differences compared to the TB80 treatment. Brewing treatments were implemented utilizing a mashing temperature range of 67-70°C. Through sensory analysis, the best formulation was identified as TC70, garnering an average rating of 4.4 for overall impression, indicative of acceptability by the panelists. No significant differences were discerned when compared to treatments TB70, TB80, TC80, TC90, and TB90. Attributes such as color, transparency, liveliness, foam retention, malt aroma, hop aroma, fermentation aroma, corn aroma, alcohol aroma, sweetness, bitterness, saltiness, acidity, corn flavor, alcohol flavor, astringency, effervescence, body, aftertaste, complexity, balance, and overall impression were meticulously evaluated.
En Ecuador, las cervecerías (industriales y artesanales) importan malta para la elaboración de sus cervezas; esto se traduce a una salida de divisas por concepto de importación de esta materia prima, por lo que el presente trabajo de titulación tuvo como objetivo formular una cerveza artesanal de maíz tipo Ale con sustitución parcial de malta de maíz por malta de cebada como alternativa a la producción local de cerveza y a la importación de maltas y que sea aceptable sensorialmente por los consumidores. Para la elaboración de la cerveza se trabajó con una formulación base tomando como referencia los ingredientes de la cerveza estilo American Brown Ale que presenta una apariencia oscura brindada por las maltas oscuras, característico aroma a lúpulo y cuerpo. Se realizó un diseño de mezclas con el programa Desing Expert para cada variedad de maíz, donde los factores para la variedad «chulpi» fueron el porcentaje de malta de maíz chulpi (% MC), malta de cebada Pale Ale (%MP) y para la variedad «blanco blandito» fueron el porcentaje de malta de maíz blanco blandito (% MB), malta de cebada Pale Ale (% MP), la variable de respuesta fue la impresión global. Las pruebas estadísticas fueron realizadas con un nivel de confianza del 95 % en el programa estadístico Minitab ® versión 19.Se maltearon ambas variedades de maíz mediante adaptación del proceso de malteado de cebada, siendo los parámetros por controlar, temperatura, tiempo y humedad (38 °C – 31 °C, 3 - 5 días y 53 % HR), terminado este proceso se obtuvo el 93 % y 85 % de maíz germinado en las variedades «chulpi» y «blanco blandito», respectivamente., Para el secado se controló el tiempo y temperatura (24 horas y 65 °C). Se obtuvo el análisis proximal de cada variedad de maíz malteado (humedad, hidratos de carbono, proteína, lípidos, fibra, ceniza, acidez y pH), encontrando mayor concentración de hidratos de carbono en la variedad «blanco blandito». Se compararon los rendimientos de los tratamientos aplicados, dando como tratamiento más eficiente a TC70 que corresponde a la variedad «chulpi» con un 70 % de maíz malteado y un 30 % de malta de cebada; por otro lado, en la variedad «blanco blandito» se obtuvo un mejor rendimiento en el tratamiento TB70. No obstante, no se encontraron diferencias significativas con el tratamiento TB80. Para la elaboración de cerveza se aplicaron los tratamientos de estudio, empleando una temperatura de maceración de 67 – 70 °C. Se identifico la mejor formulación mediante análisis sensorial, esta fue TC70 con una media de 4,4 como calificación en la impresión global, lo que corresponde a que el producto presenta una aceptabilidad por parte de los panelistas; no se encontraron diferencias significativas con los tratamientos TB70, TB80, TC80, TC90 Y TB90, además se evaluaron los atributos de color, transparencia, vivacidad, retención de espuma, Aroma a malta, Aroma a lúpulo, Aroma a fermentación, Aroma a maíz, Aroma a alcohol, dulzor, amargor, salado, acidez, sabor a maíz, sabor a alcohol, astringencia, efervescencia, cuerpo, regusto, complejidad, equilibrio e impresión global.
Keywords: CERVEZA ARTESANAL; MAIZ; AMERICAN BROWN ALE; ANALISIS SENSORIAL